Low input sustainable agriculture: A viable climate-smart option for boosting food production in a warming world. (August 2020) - Sarkar, Deepranjan; Kar, Saswat Kumar; Chattopadhyay, Arghya; Shikha,; Rakshit, Amitava; Tripathi, Vinod Kumar; Dubey, Pradeep Kumar; Abhilash, Purushothaman Chirakkuzhyil
Highlights: Climate change is negatively affecting the agricultural systems. Low input sustainable agriculture (LISA) is proposed as a viable option. LISA enhance the resilience of agricultural systems. International initiatives are needed for large-scale adoption of LISA. Abstract: Maximizing food production for feeding a rapidly growing human population while minimizing critical resource use and soil quality degradation is a major challenge for global sustainability. Sustainable agricultural practices based on low-external input is of paramount importance for reducing environmental trade-offs and planet healthy food production. Therefore, a critical assessment was made on viable low-input technologies aimed to reduce the negative effects of agricultural production as well as the use of various crop simulation models for forecasting the agricultural production under changing climatic scenario. While crop simulation models are helpful for predicting the growth and yield of individual crops under current as well as futuristic scenarios, it is difficult to model the response of multiple cropping systems under changing climatic conditions. As a matter of fact, the developing countries, majorly dependent on agriculture are most vulnerable to climate change. The increasing price of agrochemicals is another setback for subsistence farmers in resource-poor nations. In this backdrop, the current review aimed to assess the impact of climate change on agriculture, and the role of low input sustainable agriculture (LISA) for ensuring the food security while safeguarding the critical natural resources for human-wellbeing and also for attaining UN-Sustainable Development Goals. In addition, evidence-based impacts of LISA in emerging economies from Africa and South Asia are highlighted and suitable ecological indicators for measuring the sustainability of such LISA are addressed in brief. We conclude that the large-scale implementation of LISA will facilitate agricultural sustainability, and therefore, suitable policy frameworks are imperative for its worldwide adoption.